Simultaneous Quantification of Berberine Hydrochloride and Fibrauretine Tablets in Rat Urine, Feces, Bile and Plasma by HPLC/DAD - Chen1, Xiaoshuang; Li2, Gaofeng; Hu1, Xujia (Asian Journal of Chemistry, 2014)
Isoquinoline alkaloids i.e., berberine and palmatine are bioactive components of berberine hydrochloride tablets and fibrauretine tablets, respectively. For pharmacological and pharmacokinetics purposes, a simple, rapid and sensitive HPLC/DAD method was employed to measure them in rat urine, feces, bile and plasma. After simple deproteinization by acetonitrile, the ethyl acetate/methanol extract was directly analyzed by HPLC/DAD using a kromasil C18 column (200 × 4.6 mm 5 μm) with UV detection at 265 nm, with the mobile phase comprising 0.2 % phosphoric acid buffer-acetonitrile (74:26, v/v), at a flow rate of 1 mL min-1. Calibration curves of palmatine hydrochloride and berberine hydrochloride in rat urine, feces, bile and plasma were linear over the concentration range of 0.3-75 ng/mL. After oral administration of 30 mg/kg berberine hydrochloride tablets and fibrauretine tablets, cumulative excretion amount of palmatine hydrochloride and berberine hydrochloride in rat plasma were 10.14 ± 0.71 and 0.13 ± 0.06 ng at 24 h, respectively. The cumulative amounts of palmatine hydrochloride and berberine hydrochloride in rat urine reached 1.18 ± 0.28 and 16.32 ± 0.43 ng at 36 h after dosing, respectively. The results showed for their pharmacological differences study. Validation revealed that the method was specific, accurate and precise. The fully validated method was applied to the excretion study of berberine hydrochloride and palmatine hydrochloride in rats.